Assessment of the Surgical Outcomes of the Distal Humerus Intra-Articular Fractures - Bhatta, Keshav Raj; Kandel, Rajan; Chaudhary, Durgesh; Shrestha, Bishal (Journal of Multidisciplinary Research Advancements, 2025)
Fractures of the distal humerus account for 2-6% of all fractures and pose significant challenges due to articular involvement, comminution, and osteopenia. This study evaluates the functional and radiological outcomes of intra-articular distal humerus fractures (AO Type C) managed with open reduction and internal fixation using orthogonal locking compression plates through a posterior approach with chevron olecranon osteotomy. In this prospective study, 30 patients (20 males, 10 females) with Type C distal humeral fractures (C1 = 10, C2 = 16, C3 = 4) underwent surgical treatment and were followed for a mean duration of 6 months. Causes included motor vehicle accidents (21 cases), accidental falls (7 cases), and assault (2 cases). The mean time to radiological union was 12.7 weeks. Functional outcomes assessed via the Mayo Elbow Performance Score (MEPS), which showed excellent in 12 cases, good in 10, fair in 4, and poor in 4, yielding a 73.3% good to excellent outcome rate. Complications included ulnar nerve paraesthesia (4 cases), superficial infection (4 cases), heterotopic ossification (4 cases), elbow stiffness (2 cases), and hardware prominence (2 cases). Operative management of Type C distal humerus fractures with bicolumn orthogonal locking plates provides stable fixation, facilitates early mobilisation, and results in a high union rate with satisfactory functional outcomes and acceptable complication rates.